2009
DOI: 10.1071/rd08193
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrates and amino acids influence oocyte quality in dairy heifers

Abstract: The objective of the present experiment was to determine whether increasing plasma insulin by different nutritional regimes affects oocyte quality. Holstein dairy heifers (eight per treatment) were assigned, using a two times two factorial design, to diets containing either low or high dietary leucine and either low or high dietary starch. Each heifer underwent six sessions of ovum pick-up beginning 25 days after introduction of the diets. Oocyte quality was assessed by development to the blastocyst stage in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In dairy heifers, it was shown that a high-starch diet had negative effects on oocyte developmental competence, and these were avoided when leucine intake was increased [193]. Crude protein overfeeding also compromises the subsequent capacity of bovine oocytes to develop to blastocysts, probably via direct toxic effects of elevated ammonia and urea concentration in the follicular environment [194, 195].…”
Section: Methodsmentioning
confidence: 99%
“…In dairy heifers, it was shown that a high-starch diet had negative effects on oocyte developmental competence, and these were avoided when leucine intake was increased [193]. Crude protein overfeeding also compromises the subsequent capacity of bovine oocytes to develop to blastocysts, probably via direct toxic effects of elevated ammonia and urea concentration in the follicular environment [194, 195].…”
Section: Methodsmentioning
confidence: 99%
“…A significant proportion of the moderately fat and overfed animals were hyperinsulinaemic. Rooke et al (2009) subsequently used a factorial design to alter insulin levels in dairy heifers. They found that a high-starch diet had adverse effects on oocyte quality which were associated with a high plasma insulin : glucagon ratio but that these were avoided when leucine intake was also increased.…”
Section: Nutrition and Growth Ratementioning
confidence: 99%
“…High-energy diets have also adverse effects on early embryonic development and these effects may be programmed even before fertilization, during the acquisition of oocyte developmental competence in the follicle (Rooke et al, 2009). In the high-yielding dairy cow, supplementary dietary carbohydrates can reduce the quality of oocytes and the development of embryos, resulting in fewer blastocyst cells and a lower rate of blastocyst production (Fouladi-Nashta et al, 2005).…”
Section: Overnutrition and Oocyte Qualitymentioning
confidence: 97%